Cross-sectional multicentre study on the cohort of all the French junior lecturers in general practice. (1st January 2018) - Barais, Marie; Laporte, Catherine; Schuers, Matthieu; Saint-Lary, Olivier; Frappé, Paul; Dibao-Dina, Clarisse; Darmon, David; Bouchez, Tiphanie; Gelly, Julien
Abstract: Background: General practice became an academic discipline quite recently in many western countries. In France, junior lecturer work is specified in a three-part mandate: medical work in general practice, teaching in the university, and research. Since 2007, 130 junior lecturers have been appointed in general practice. The aim of the creation of junior lecturer status was to align general practice with other specialties and to develop research and education in primary care. Objectives: To describe the healthcare, teaching and research undertaken by junior lecturers in general practice, practising in October 2014. Methods: A cross-sectional multicentre study using an online self-administered questionnaire on the cohort composed of all the junior lecturers in general practice with open questions and the qualitative analysis of written verbatim accounts. Results: Of the 95 junior lecturers practising at the date of the study, 75 (79%) responded; average age 32 years; gender ratio (F/M) 2.4:1. They spent five, two and three half-days per week respectively in healthcare, teaching and research. The healthcare activity was predominantly carried out in the community (73%). Thirty-nine per cent worked as part of a multi-professional team taking on 50 consultations per week. Most of the educational work involved lecturing and mentoring students specializing in general practice (median 86 hours per year). Research output increased during the fellowship. Research topics were varied and relevant to the disciplinary field. Conclusion: During the fellowship, the balancing, and even the reinforcement, of healthcare and research contributions were accompanied by a significant investment in educational provision.